SISTEM MONITORING SERVER BERBASIS ANDROID DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN REMBANG - Moh Rifqi Azizi; Septia Lutfi; Agus Purwanto (Journal of Information System and Computer, 2022)
In this research, identification has been made to make an Android-based server monitoring application using the System Development Life Cycle Technique. This research is based on the work of monitoring servers to find out which servers are down / offline or which servers are up / online. This research uses descriptive research method. Descriptive research is generally carried out with the aim of systematically describing the facts and characteristics of the object and subject being studied appropriately. The stages carried out in the descriptive model include stages such as analysis, design, implementation, evaluation, improvement, and development. Based on testing the quality of the software for functionality aspect, the server monitoring information system has fulfilled the overall function with a success percentage of 100%. Based on the results of software quality testing on the usability aspect, it produces a total score of 893 which is converted into an index scale getting a value of 94%. Then a percentage of 94% is converted into a qualitative scale resulting in a feasible rating scale. So it can be concluded that the server monitoring information system has met the usability aspect. The result of this research is an android based software which can monitor server. Users can find out which servers are up / online or which servers are down / offline. Users can monitor server conditions in realtime